Adjustment of phosphorus concentration to increase growth and yield of cherry tomato using hydroponic drip system - Cecep Hidayat (Jurnal Agro, 2018)
The phosphorus element plays an essential role in plant growth both at the vegetative and generative phases, so its concentration modification in the nutrient solution is necessary to stimulate vegetative growth and crop yield. The research aimed to know the influence of different phosphorus concentrations on growth and yield of cherry tomato using a hydroponic drip irrigation system, conducted from February to June 2017 at Green House Research Station of  Universitas Padjajaran Jatinangor using Completely Randomized Design with five treatments and five replications. The treatments were: phosphorous concentration of 100 ppm (P/N ratio 0.4), 125 ppm (P/N ratio 0.5), 150 ppm (P/N ratio 0.6), 175 ppm (P/N ratio 0.7), and 200 ppm (P/N ratio 0.8). The results showed that the increasing concentration of phosphorus improved crops height at the end of the vegetative phase, increased the number of flowers from the beginning to the end of the generative period, was able to prevent the flower fall, enhanced harvest index and weight of tomato fruit significantly at harvest time. Application of 200 ppm phosphorus concentration can increase growth and yield of cherry tomato.